Treatise on geophysics - Schubert, Gerald (Elsevier, 2007)
The Treatise on Geophysics on a comprehensive summary of the present state of geophysics. It deals with all major parts of Solid-Earth Geophysics, including a volume on the terrestrial planets and moons in our solar system.